Effect of rivaroxaban and dabigatran on platelet functions: in vitro study. Issue 183 (November 2019) - Jourdi, Georges; Bachelot-Loza, Christilla; Mazoyer, Elisabeth; Poirault-Chassac, Sonia; Duchemin, Jerome; Fontenay, Michaela; Gaussem, Pascale
Abstract: Introduction: Clinical benefit-risk balance of direct oral anticoagulants (DOAC) in atherothrombosis prevention differs between anti-Xa and anti-IIa drugs and their specific effect on platelet functions remains controversial. We hence investigated rivaroxaban and dabigatran effect on platelets in identical experimental conditions. Materials and methods: Blood of fifteen healthy volunteers was spiked with DOAC which plasma concentrations were measured by specific anti-Xa or anti-IIa assays. Light transmission aggregometry measured in platelet-rich plasma used low doses of agonists: 0.5 mM arachidonic acid, 2.5 μM ADP, 0.5 μM epinephrine, 0.8 μg/ml collagen, 7.5 μM TRAP-6 and 0.5 pM tissue factor in the presence of H-Gly-Pro-Arg-Pro-OH to prevent fibrin polymerization. Platelet adhesion on collagen fibres was evaluated in whole blood under flow. Same experiments were reproduced in the presence of aspirin. Results: Median [95% CI] plasma concentrations were of 28 [23–36], 128 [119–144] and 321 [293–361] ng/ml for rivaroxaban and 39 [34–45], 171 [166–193] and 353 [349–382] ng/ml for dabigatran. DOAC did not modify platelet aggregation or adhesion on collagen fibres at any tested concentrations. However, they delayed platelet aggregation secondary to coagulation activation with a more potent effect with dabigatran ( p < 0.001). Aspirin did not modify DOAC effect. Conclusion: Efficacy of combining DOAC and aspirin in atherothrombosis prevention would not stem from a direct antiplatelet effect of the formers but to their additive inhibitory effect on platelet aggregation secondary to coagulation activation. This effect differs according to DOAC molecules and may also result from the pleiotropic roles of the different coagulation factors targeted by DOAC.